Abatement Addiction: A Case Study on Jersey City's Municipal Tax Abatements, Urban Gentrification and the Politics of Rights - Wharton, Jonathan (American Political Science Association, Social Science Research Network, 2011)
As New Jersey’s second largest city, Jersey City has experienced a surge in urban redevelopment and new development, particularly its downtown wards closest to New York City. Situated on the Hudson River directly across from downtown New York City, Jersey City is an ideal location for New Jersey developers and realtors to redevelop in order to attract New York City’s financial sector employees and individuals desiring more living space at lower rental or mortgage costs. In other words, downtown Jersey City exemplifies urban gentrification. In the last twenty years, several public policies helped spur waterfront development to attract potentially wealthier residents. In an effort to lure developers and investors, Jersey City officials relied heavily on municipal tax abatements to offset increasingly high property taxes. So after two decades, has Jersey City demonstrated that Payment in Lieu of Taxes (PILOT), tax abatements and other tax policy incentives are in fact feasible in terms of the following questions: What have been the implications of these policies? Who benefited from and who was marginalized from these policies? This paper examines the rising concerns surrounding tax abatements and other pro-development tax policies. By examining a medium sized city like Jersey City, this case study is especially useful in understanding the significant issues and shortcomings with urban redevelopment tax incentives. Too often these incentives benefit a political and financial elite at the economic expense and loss of political rights of long-term residents and renters.
Keywords: New Jersey; dept.psc; gentrification; tax abatements; urban development; urban politics; ⛔ No DOI found

Democracy in New England: a community politics reader - Wharton, Jonathan L. (Cognella Academic Publishing, 2018)
Keywords: New England; Politics and government; dept.psc; faculty_collection

Unique Policymaking in Action: The District Council and the Legislative Process - Wharton, Jonathan L. (Law, Politics, and African Americans in Washington, DC, 2010)
Law, Politics, and African Americans in Washington, DC explores the legal challenges and triumphs of African Americans and law and politics in Washington, DC, a city whose majority population comprises African Americans. It examines the interconnection between law and politics in Washington, DC, because it is vital to know the legal conditions under which the African American residents of the most powerful city in the world live, based on sound empirical evidence. Law, Politics, and African Americans in Washington, DC addresses two major questions: - Why study African Americans in terms of law and politics? - Why examine law and politics at the local level, in this case Washington, DC?
Keywords: dept.pch

Political Erosion in 'The Land of Steady Habits': Party Politics in Connecticut's 2018 Gubernatorial Election - Wharton, Jonathan L. (New England Journal of Political Science, 2019)
Keywords: dept.psc; peer-reviewed; ⛔ No DOI found

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, Jonathan L. (Palgrave Macmillan, 2013)
Keywords: Booker; Cory; Metropolitan government; Case studies; Case studies; Mayors; Case studies; Newark (N.J.); Case studies; Post-racialism; Election; African American mayors; New Jersey; Newark; Newark; Urbanization; Political aspects; Politics and government; Newark (N.J.); Race relations; United States; dept.psc; faculty_collection